2021
DOI: 10.1007/s00181-020-01990-5
|View full text |Cite
|
Sign up to set email alerts
|

The volatility of Bitcoin and its role as a medium of exchange and a store of value

Abstract: Bitcoin is designed as a peer-to-peer cash system. To work as a currency, it must be stable or be backed by a government. In this paper, we show that the volatility of Bitcoin prices is extreme and almost 10 times higher than the volatility of major exchange rates (US dollar against the euro and the yen). The excess volatility even adversely affects its potential role in portfolios. Our analysis implies that Bitcoin cannot function as a medium of exchange and has only limited use as a risk-diversifier. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(66 citation statements)
references
References 38 publications
2
62
0
2
Order By: Relevance
“…In conventional fiat monetary form, central bodies and banks control the budgetary framework. But with cryptocurrencies these exchanges can be prepared and approved by a conveyed and open organize that is claimed by no one (Baur & Dimplf, 2021). Cryptocurrencies are based on distributed network technology.…”
Section: Decentralized No Central Authoritymentioning
confidence: 99%
See 1 more Smart Citation
“…In conventional fiat monetary form, central bodies and banks control the budgetary framework. But with cryptocurrencies these exchanges can be prepared and approved by a conveyed and open organize that is claimed by no one (Baur & Dimplf, 2021). Cryptocurrencies are based on distributed network technology.…”
Section: Decentralized No Central Authoritymentioning
confidence: 99%
“…Bitcoin keeps on setting untouched highs for quite a while, while Ethereum guarantees to utilize Blockchain to interrupt every monetary instrument and business forms. Baur & Dimplf (2021) investigated whether Bitcoin can replicate standard money forms. They suggested that since Bitcoin is not backed by Gold or any regulatory authority it cannot act as a medium of exchange and has a restricted utilize as a risk diversifier.…”
Section: Crypto Currency Versus Standard Currencymentioning
confidence: 99%
“…This erratic price behavior would force constant repricing of the items on sale (e.g., the labels of all products in supermarket shelves) rendering it impossible to use Bitcoin as a unit of account and an undesirable instrument to denominate and settle debts. Also, the extreme volatility of Bitcoin is inconsistent with a currency acting as a store of value, at least in the short-term [30][31][32]. According to [33] (p. 98) "at most, cryptocurrencies can be viewed as a new kind of tradable speculative asset, which can work as imperfect substitutes for traditional currencies".…”
Section: From Bitcoin To Central Bank Digital Currencies (Cbdcs)mentioning
confidence: 99%
“…On the one hand, supervisory offices send warning signals, especially to private individuals, against succumbing to the vision of obtaining quick extraordinary profits, as well as against creating a speculative bubble on cryptocurrencies (Geuder, Kinateder and Wagner, 2019;Enoksen, Landsnes, Lučivjanská and Molnár, 2020;UKNF, 2021). On the other hand, many people see BTC and other cryptocurrencies as an effective tool for storing value (Corbet, Hou, Hu, Larkin and Oxley, 2020;Baur and Dimpf, 2021).…”
Section: Introductionmentioning
confidence: 99%